God as political philosopher : Buddha's challenge to Brahminism - Ilaiah, K (Samya ; Distributed by Popular Prakashan, 2001)
This research work posits Gautama Buddha as a political thinker. It performs the task of interrogating historically the Buddhist and brahminical worldviews and shows that Buddha constructed a very powerful speculative political philosophy which can form the basis of reconstructing ancient Eastern political philosophy itself.